Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)
Trace DNA detection methods are increasingly applied to biomonitoring, in conservation, biosecurity, and wildlife forensic sciences. Reptiles are high risk invasive alien species that can cause damaging environmental impacts, yet the dynamics around terrestrial reptile DNA deposition and subsequent detection are poorly understood. Concerns around the role of the pet trade in introducing key reptile pests have resulted in calls for greater biosecurity surveillance and biomonitoring tools. Emerging studies have explored the applications of trace DNA and environmental DNA (eDNA) to reptile detectability, but questions remain around DNA persistence, sample storage, and DNA degradation through time influencing biosecurity compliance uptake. Here we consider Pantherophis guttatus (American corn snake), a key vertebrate pest species in Australia, as a model organism for the study of trace DNA detection over time. Our study focussed on the application of a recently developed corn snake LAMP assay for DNA detection from biosecurity relevant samples, with a particular focus on wildlife compliance for captive reptiles and shed skin samples subject to varied storage and environmental conditions. Experiments were conducted with (i) shed skin subject to a range of storage and treatment conditions over a 10-week period, (ii) trace DNA samples deposited on newspaper, plastic, glazed terracotta, and glass for 0 to 168 h post live snake presence, and (iii) shed skin samples subject to varying environmental conditions over an 8-week period. DNA remained detectable for up to 10 weeks under different storage conditions when extracted from shed skin and for up to 168 h after live reptile contact. DNA extracted from shed skin samples subject to varied environmental conditions was detectable up to 8-weeks post deposition with increasing times to detection. Our findings strengthen the case for trace DNA detection methods being applied to monitoring of terrestrial snakes, particularly for rapid compliance, monitoring, and environmental biosecurity.